Forecasting European Gas Supply Selected results from EUGAS model and historical verification - David Bothe; Andreas Seeliger (Institute of Energy Economics at the University of Cologne (EWI), 2005)
The common application of EUGAS, a long-term, dynamic, interregional linear optimization model, is the projection of European natural gas supply up to 2030. Based on current expectations regarding future demand, supply costs and reserves, the model results comprise production and transport volumes, changes in infrastructure and marginal costs of supply, covering the EU-25 plus the main non-EU supply countries. In the reference run a significant increase in Middle Eastern gas is projected while generally a growing share of volume will be imported via LNG. In order to assess validity of these projections a model run was conducted re-simulating the evolution of European gas market from 1960-2000. While the general results are predominantly in line with the historical development, one of the main findings is that the current strong position of FSU-gas in Western Europe contradicts cost minimal calculation.
Keywords: N74; Q41; L95; C61; 330; Natural Gas; European gas market; Modelling